Atomic-scale tomography of semiconductor nanowires. (December 2015) - Qu, Jiangtao; Ringer, Simon; Zheng, Rongkun
Abstract: Atomic-scale structure and composition is critical to understand the novel properties and to realize the technological applications of semiconductor nanowires. This paper reviews the latest progresses in atomic-scale tomography of various semiconductor nanowires for application in electronics, photonics, thermoelectrics and photovoltaics. In practice, specimen preparation is usually the obstacle for the atomic-scale tomographic experiment. In this regard, promising specimen preparation methods from semiconductor nanowires are also summarized and compared. The unprecedented information extracted from 3D reconstruction of tomographic data provides deep insight into semiconductor nanowires and enables understanding of properties and optimization of growth.